Can presidential misinformation on climate change be corrected? Evidence from Internet and phone experiments. (August 2019) - Porter, Ethan; Wood, Thomas J.; Bahador, Babak
Can presidential misinformation affect political knowledge and policy views of the mass public, even when that misinformation is followed by a fact-check? We present results from two experiments, conducted online and over the telephone, in which respondents were presented with Trump misstatements on climate change. While Trump's misstatements on their own reduced factual accuracy, corrections prompted the average subject to become more accurate. Republicans were not as affected by a correction as their Democratic counterparts, but their factual beliefs about climate change were never more affected by Trump than by the facts. In neither experiment did corrections affect policy preferences. Debunking treatments can improve factual accuracy even among co-partisans subjected to presidential misinformation. Yet an increase in climate-related factual accuracy does not sway climate-related attitudes. Fact-checks can limit the effects of presidential misinformation, but have no impact on the president's capacity to shape policy preferences.